Comparative Benefits of Primary Percutaneous Coronary Intervention Versus Onsite Fibrinolytic for Patients With ST‐Segment–Elevation Myocardial Infarction: A Quasi‐Experimental Study - Shuduo Zhou; Siwei Xie; Binquan You; Dingcheng Xiang; Weiyi Fang; Michael G. Trisolini; Kenneth A. Labresh; Sidney C. Smith; Zhi‐Jie Zheng; Yinzi Jin; Feng Liu; Yong Huo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Primary percutaneous coronary intervention (PCI) is the preferred reperfusion strategy compared with onsite fibrinolytic therapy (O‐FT) for ST‐segment–elevation myocardial infarction when delivered promptly. However, the contemporaneous data to inform the comparative benefits of primary PCI versus O‐FT, especially in developing countries, have been largely understudied. Methods We used data from the National Chest Pain Center Program (NCPCP), the largest nationwide registry in China, including patients with ST‐segment–elevation myocardial infarction treated with primary PCI or O‐FT from January 2016 to December 2022. Patients were matched using propensity scores, and the PCI‐related delay was defined as the difference between the observed door‐to‐wiring time and the door‐to‐needle time. Mortality outcomes were assessed at different delay intervals (<60 minutes, 60–90 minutes, >90 minutes). Subgroup analyses were conducted based on age, infarction location, and Killip classification. Results In 19 334 matched patients, primary PCI demonstrated a significant mortality benefit over O‐FT when PCI‐related delays were <60 minutes (2.34% versus 6.01%). However, this advantage diminished when delays exceeded 90 minutes. The critical threshold at which PCI lost its mortality benefit was identified as 119.51 minutes (door‐to‐wiring time – door‐to‐needle time). Subgroup analyses showed that older patients, patients with anterior infarction, and those with a higher Killip class appeared to have lower equipoise thresholds. Conclusions Primary PCI offers a mortality benefit compared with O‐FT in patients with timely treated ST‐segment–elevation myocardial infarction, but treatment delays can mitigate this benefit. In settings with prolonged treatment delays, immediate fibrinolysis may be a more effective strategy. Treatment decisions should incorporate both patient characteristics and health care system constraints to optimize ST‐segment–elevation myocardial infarction outcomes.